Control of invasive species for the conservation of biodiversity in Mediterranean islands. The LIFE PonDerat project in the Pontine Archipelago, Italy. (3rd September 2017) - Celesti-Grapow, Laura; Abbate, Giovanna; Baccetti, Nicola; Capizzi, Dario; Carli, Emanuela; Copiz, Riccardo; Frondoni, Raffaella; Giunti, Michele; Gotti, Camilla; Iberite, Mauro; Monaco, Andrea; Petrassi, Fabrizio; et al.
Abstract: We present the EU LIFE PonDerat project, which is aimed at restoring the natural ecosystems of the Pontine Archipelago, a group of islands located off the western coast of Italy. The spread of invasive species is a major environmental threat on these islands, which are rich in rare habitats and endemic species and are important sites for the conservation of Mediterranean biodiversity. The project focuses on the conservation of species and habitats that are protected by EU laws but are currently threatened by introduced plants and animals. The main targets of the control measures are black rats, feral goats, mouflons and invasive plants of the genus Carpobrotus . Conservation measures focus on the shearwaters Puffinus yelkouan and Calonectris diomedea, which are endemic to the Mediterranean and are listed in Annex I of the European Bird Directive. Conservation measures also focus on island habitats of great biogeographical value, which are listed in Annex I of the European Habitats Directive and are seriously threatened by introduced herbivores and by invasive plants. The main outcome expected from this project is that the restoration of ecosystem functions will enhance the breeding success and population size of shearwaters and lead to the recovery of target habitats.